Anti-inflammatory potential of aeroplysinin-1, a bioactive compound isolated from the sponge Aplysina aerophoba - Bravo-Ruiz, Inés; Bernal, Manuel; Manrique-Poyato, Maria Inmaculada; Rodríguez-Quesada, Ana María; Medina-Torres, Miguel Ángel; Castilla, Laura; Martínez-Póveda, Beatriz Amparo (43 Congreso Anual SEBBM, 2021)
Aeroplysinin-1 (Apl-1) is a brominated compound isolated from the marine sponge Aplysina aerophoba that has been shown to possess bioactive effects with a broad spectrum of action in in vitro and in vivo assays. Included in its pleiotropic activity are anti-tumor, anti-angiogenic, pro-apoptotic [1] and anti-oxidant effects [2], making Apl-1 a natural compound with very promising properties for its use as a potential therapeutic agent. In addition to the aforementioned effects, our group explored the role of Apl-1 in inflammation, a process related to numerous highly prevalent pathologies, such as cancer and atherosclerosis, showing the first evidence of its anti-inflammatory potential [3]. In this work, our group delves into the anti-inflammatory effect of Apl-1 in the context of vascular endothelium and provides new data regarding the molecular mechanism underlying this activity. The characterization of the mechanism of action points to the modulatory effect of Apl-1 on pathways involved in endothelial activation during the development of inflammation, experimental evidence that opens the door to the potential use of this compound as an anti-inflammatory agent.
Contribución a Congreso (póster)
Keywords: Medicamentos - Congresos; Aeroplysinin-1